Penyelesaian Sengketa Tanah Wakaf Di Kecamatan Selebar Kota Bengkulu Dalam Perspektif Hukum Islam Dan Hukum Positif - Ibnu Masud; Irsal Irsal (Al-Khair Journal: Management Education, 2022)
Abstract : The purpose of this study is to find out and describe the procedures for resolving waqf land disputes in the Selebar District of Bengkulu City in the perspective of Islamic law and positive law. This study uses field research methods (field research). The type of approach used in this study is a qualitative descriptive approach. The type of research used by the researcher is field research using a qualitative descriptive approach. The research was conducted from May to June 2021 with the location in Selebar District, Bengkulu City, Bengkulu Province, Indonesia. The results of the study indicate that the parties, among others, are through Deliberation, Arbitration, Mediation and Litigation whose implementation is adjusted to the situation and conditions at the time of the dispute. In the settlement of waqf land disputes in a sub-district as wide as the city of Bengkulu, Nazir and the disputing parties prefer to use the peaceful way, this according to the author is in accordance with Islamic law, but some are resolved by peaceful means and there are also those whose decisions are suspended or there is no certainty. . From several cases of waqf land disputes in Selebar District, Bengkulu City after studying the data that the author has collected. The author concludes as follows: 1.) Settlement of waqf land disputes in Sebar District, Bengkulu City. Settlement of disputes through non-litigation and litigation channels in accordance with Islamic law and positive law. 2.) Settlement of land disputes in the Selebar District of Bengkulu City, the perspective of Islamic law is also appropriate.Keywords: Waqf Land Dispute, Broad, Positive Law and Islamic Law. Abstrak : Adapun tujuan penelitian ini adalah untuk mengetahui dan mendeskripsikan tata cara dalam penyelesaian sengketa tanah wakaf di Kecamatan Selebar Kota Bengkulu Dalam Perspektif hukum Islam dan hukum Positif. Penelitian ini menggunakan metode penelitian lapangan (field research). Jenis pendekatan yang digunakan dalam penelitian ini adalah pendekatan deskriptif kualitatif. Adapun jenis penelitian yang digunakan oleh peneliti adalah penelitian lapangan (field research) dengan menggunakan pendekatan deskriptip kualitatif. Penelitian dilakukan mulai bulan Mei sampai dengan bulan Juni Tahun 2021 dengan lokasi di Kecamatan Selebar, Kota Bengkulu, Provinsi Bengkulu, Indonesia. Hasil penelitian menunjukkan bahwa para pihak antara lain melalui Musyawarah, Arbitrase, Mediasi dan Litigasi yang pelaksanaannya disesuaikan dengan situasi dan kondisi pada saat terjadi sengketa. Dalam penyelesaian sengketa tanah wakaf di kecamatan seluas kota Bengkulu, Nazir dan para pihak yang bersengketa lebih memilih menggunakan jalan damai, hal ini menurut penulis sudah sesuai dengan syariat Islam, namun ada yang diselesaikan dengan jalan damai dan ada juga yang keputusannya digantung atau tidak ada kepastiannya. Dari beberapa kasus sengketa tanah wakaf di Kecamatan Selebar Kota Bengkulu setelah mempelajari data-data yang telah penulis kumpulkan. Penulis menyimpulkan sebagai berikut: 1.) Penyelesaian sengketa tanah wakaf di Kecamatan Sebar Kota Bengkulu. Penyelesaian sengketa melalui jalur non litigasi dan litigasi sesuai dengan hukum Islam dan hukum positif. 2.) Penyelesaian sengketa tanah di Kecamatan Selebar Kota Bengkulu, perspektif hukum Islam juga sesuai.Kata kunci : Sengketa Tanah Wakaf, Selebar, Hukum Positif dan Hukum Islam.